2002
DOI: 10.1007/s00424-001-0770-0
|View full text |Cite
|
Sign up to set email alerts
|

Diet supplementation with vitamin E, vitamin C and β-carotene cocktail enhances basal neutrophil antioxidant enzymes in athletes

Abstract: Exercise increases oxygen consumption and causes a disturbance of intracellular pro-oxidant-antioxidant homeostasis. Few data are available as to the cumulative effects of exercise on the antioxidant defenses of the neutrophil. We studied the effects of 90 days' supplementation with placebo or an antioxidant cocktail of vitamin E (500 mg/day) and beta-carotene (30 mg/day) and the last 15 days also with vitamin C (1 g/day) on sportsmen's basal neutrophil antioxidant defenses. We analyzed the activities of catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 40 publications
3
45
2
2
Order By: Relevance
“…SOD together with GSH-Px and CAT, are the first-line antioxidant protection of any cell (Halliwell 2006). Our findings demonstrated that the combination of antioxidant vitamins stimulated the activity of antioxidant enzymes in erythrocytes of the supplemented sows, which was consistent with the earlier studies of other authors (Rodrigez-Porcel et al 2002, Tauler et al 2002. Rodrigez-Porcel et al (2002) observed increased activities of GSH-Px, SOD and CAT in pig myocardial tissues after a 12-week supplementation with vitamin E at a dose of 100 mg/kg fodder and vitamin C at a dose of 1g per animal.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…SOD together with GSH-Px and CAT, are the first-line antioxidant protection of any cell (Halliwell 2006). Our findings demonstrated that the combination of antioxidant vitamins stimulated the activity of antioxidant enzymes in erythrocytes of the supplemented sows, which was consistent with the earlier studies of other authors (Rodrigez-Porcel et al 2002, Tauler et al 2002. Rodrigez-Porcel et al (2002) observed increased activities of GSH-Px, SOD and CAT in pig myocardial tissues after a 12-week supplementation with vitamin E at a dose of 100 mg/kg fodder and vitamin C at a dose of 1g per animal.…”
Section: Discussionsupporting
confidence: 82%
“…Rodrigez-Porcel et al (2002) observed increased activities of GSH-Px, SOD and CAT in pig myocardial tissues after a 12-week supplementation with vitamin E at a dose of 100 mg/kg fodder and vitamin C at a dose of 1g per animal. Tauler et al (2002) showed that supplementation with an antioxidant cocktail of vitamin E, vitamin C and β-carotene for 90 days significantly increased the activity of SOD and CAT in neutrophils of sportsmen. In turn, Zaidi and Banu (2004) found that both vitamin E alone and in combination with vitamins A and C was effective in enhancing the activities of SOD and CAT in stressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…KATAMOTO et al (1998) observaram uma tendência de maior atividade da GSHPx com a suplementação injetável de selênio e vitamina E, nas doses de: 0,1mg kg -1 e 2,72UI kg -1 , respectivamente, em cabras sob estresse térmico. No entanto, TAULER et al (2002) avaliaram a suplementação via oral de vitamina E, na dose de 500mg/dia, associada a outros agentes antioxidantes (vitamina C e beta-caroteno) na dieta de atletas, verificando um aumento de 47% da atividade da GSHPx no grupo tratado.…”
Section: Ciência Rural V40 N3 Mar 2010unclassified
“…It has been shown that vitamins C and E may prevent the exercise-induced oxidative damage [14,15] and may diminish the post-exercise oxidative stress [15]. Synergistic effects have been described between vitamin C and E in the defense against oxidative stress, enhancing neutrophil antioxidant defences [16,17]. These cellular effects of antioxidant vitamins on neutrophils need to be mediated by their uptake from the plasma.…”
Section: Introductionmentioning
confidence: 99%